Research on Calculation Method of DC Side Capacitor Ripple Components for Three-level Inverter - ZHANG Honghao; ZHOU Ting; GUO Jijin; ZHONG Qiang; YU Qing (Kongzhi Yu Xinxi Jishu)
Ripple current of DC side capacitor affects capacity selection and life of a capacitor, and ripple voltage of capacitor affects the voltage that power device needs to bear, so analysis of capacitor ripple components is very important for the design of inverter. In this paper, by analyzing topology and modulation mode of main circuit of a three-level inverter, mathematical expressions of ripple current and ripple voltage for DC side capacitor of NPC three-level converter are derived, in which the effective value of the current is related to the modulation ratio and the load power factor, and the ripple voltage is related to the capacitance and the load power factor. In addition, the mathematical expressions have been verified by simulation. The influence of stray inductance on ripple current is also verified by the inverter test.